'Having cancer was awful but also something good came out': Post-traumatic growth among adult survivors of pediatric and adolescent cancer. (June 2017) - Zamora, Eduardo R.; Yi, Jaehee; Akter, Jesmin; Kim, Jonghee; Warner, Echo L.; Kirchhoff, Anne C.
Abstract: Purpose: The cancer experience may cultivate positive psychological changes that can help reduce distress during adult survivors of childhood and adolescent cancer life course. The aim of this study is to examine the positive impact of cancer in adult survivors utilizing posttraumatic growth as a guiding framework. Method: Participants were identified and recruited through the Utah Cancer Registry. Eligible cases were diagnosed with cancer age ≤20 years from 1973 to 2009, born in Utah, and were age ≥18 at study. Semi-structured phone interviews (N = 53) were analyzed using deductive analysis. Results: The primary five themes that emerged were similar to Tedeschi and Calhoun's (1996) themes for measuring positive effects, and were used to frame our results. The primary themes along with uniquely identified sub-themes are the following: personal strength (psychological confidence, emotional maturity), improved relationship with others (family intimacy, empathy for others), new possibilities (having passion work with cancer), appreciation for life (reprioritization), and spiritual development (strengthened spiritual beliefs, participating in religious rituals and activities). Conclusions: For survivors, cancer was life altering and for many the experience continues. Understanding survivors' complex cancer experience can help improve psychosocial oncology care. Highlights: Verifies concept and domains of posttraumatic growth from themes with adult survivors of childhood and adolescent cancer. Demonstrates that through the process of confronting child and adolescent cancer positive meaning-making can be developed. Provides recommendations of how PTG can be utilized to improve psychosocial support for survivors.